2017
DOI: 10.1021/acscatal.7b02677
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Initiation in the Phillips Ethylene Polymerization Catalyst: Ethylene Activation by Cr(II) and the Structure of the Resulting Active Site

Abstract: The structure and mechanism of the formation of sites which initiate ethylene polymerization in the atomically dispersed Phillips catalyst (Cr/ SiO 2 ) are two of the great unsolved mysteries of heterogeneous catalysis. After CO or C 2 H 4 reduction of silica-supported Cr VI ions to Cr II ions in the precatalyst, exposure to ethylene results in the formation of organoCr III sites that are capable of initiating polymerization without recourse to an external alkylating cocatalyst. In this work, a Phillips cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 80 publications
2
55
5
Order By: Relevance
“…EPR investigations of these catalysts showed that only a small amount of Cr 51 remained as an impurity after the reduction. [108][109][110] The non-Kramers Cr 21 species (S ¼ 2) was investigated using high field EPR at 106/212/317 GHz, and was reported to have a very small rhombicity for the ZFS tensor. 109 Upon ethylene polymerisation, two research groups reported different observations, albeit under slightly different conditions.…”
Section: Phillips Based Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…EPR investigations of these catalysts showed that only a small amount of Cr 51 remained as an impurity after the reduction. [108][109][110] The non-Kramers Cr 21 species (S ¼ 2) was investigated using high field EPR at 106/212/317 GHz, and was reported to have a very small rhombicity for the ZFS tensor. 109 Upon ethylene polymerisation, two research groups reported different observations, albeit under slightly different conditions.…”
Section: Phillips Based Systemsmentioning
confidence: 99%
“…However, in another study the polymerisation reaction was performed at T ¼ 80 1C and the authors reported the appearance of Cr 31 signals, characterised by the broad linewidth, centred at gB1.98 with axial symmetry, together with the loss from Cr 21 signals. 109,110 Therefore, it was concluded that the Cr 21 sites were oxidised to organo-Cr 31 species by ethylene, which initiated the polymerisation.…”
Section: Phillips Based Systemsmentioning
confidence: 99%
“…One example of a long‐standing discussion is the oxidation state of the Cr active site, which has been investigated with many different spectroscopic techniques, demonstrating that the active valency lies between 2 and 3, with the true value still being questioned by varying insights from different research groups. These differences, however, can in part be ascribed to different reaction set‐ups and different catalyst materials [33, 34, 43–46, 35–42] …”
Section: Introductionmentioning
confidence: 99%
“…Examples include model systems [22][23][24][25][26][27][28] or well-defined catalyst systems in which Cr 6 + is reduced by e. g. CO. [13,14,[29][30][31] With an array of spectroscopic techniques revealing that the oxidation state of the Cr active site lies between 2 and 3. [13,14,[39][40][41][42][43][44][45]20,[32][33][34][35][36][37][38] However, assigning a definitive oxidation state number remains a matter of debate due to the various findings from different groups, although this could be in part explained due to different catalyst materials and reaction setups. [6,20,[47][48][49]34,[36][37][38][40][41][42]46] Fortunately, with the continuous development of advanced spectroscopic and microscopic techniques, the low Cr weightloading and relatively small portion of active sites are becoming less of a problem, exemplified by elucidation of an ethylene reduced active site.…”
Section: Introductionmentioning
confidence: 99%
“…[13,14,[39][40][41][42][43][44][45]20,[32][33][34][35][36][37][38] However, assigning a definitive oxidation state number remains a matter of debate due to the various findings from different groups, although this could be in part explained due to different catalyst materials and reaction setups. [6,20,[47][48][49]34,[36][37][38][40][41][42]46] Fortunately, with the continuous development of advanced spectroscopic and microscopic techniques, the low Cr weightloading and relatively small portion of active sites are becoming less of a problem, exemplified by elucidation of an ethylene reduced active site. [18] Even though our understanding of CO and ethylene reduced Cr/SiO 2 catalysts is increasing, research towards the effects of metal-alkyl co-catalysts on the active site structure and oxidation state has only started to gain track more recently.…”
Section: Introductionmentioning
confidence: 99%